Rectangular-shaped microshield coplanar waveguides on cylindrical substrate - Karpuz, C; Görür, A; Genç, Z (John Wiley & Sons Inc, 2001)
In this study CAD-oriented analytic expressions derived by the conformal mapping method are presented, for the first time, for calculating the line parameters of a rectangular-shaped microshield CPW on a cylindrical substrate. The effect of the curvature on the line parameters is discussed. In addition, this papers results are compared with the results available in the literature for a rectangular-shaped microshield coplanar waveguide on a planar substrate. (C) 2001 John Wiley & Sons, Inc.
Keywords: microshield; coplanar waveguide; curved substrate